(untitled) (International Journal of Scientific Trends, 2024)
Today, the opportunities for further development of the Uzbek economy are very wide, and in our opinion, there is another untapped opportunity. It does not require a large investment, preparation or scientific solutions to implement it. This ancillary (additional) sector does not require special land, irrigation facilities and training. It is a mulberry tree that grows in drought-tolerant, highly saline or sandy soils. It can be maintained around roads, ditches and ditches, near apartment buildings, and in unused state reserves. Mulberry has been harvested twice a year for thousands of years, and when its leaves are cut with a twig in the spring, it is possible to grow the leaves as a feed to re-feed the silkworm both in summer and autumn. In addition, silkworms can be used to grow cocoons from mulberry leaves, raisins, halva, juice, jam (vareng’e), wine, and mulberry grass can be used as fuel. Our people have known for a thousand years that high-quality natural silk fabrics are grown through deep processing of silkworm cocoons. Fabrics such as satin and adras are woven from it at home.